Comparaison de deux systèmes de rotation de postes dans le cadre de la prévention des troubles musculosquelettiques - Anne Gerling; Agnès Aublet-Cuvelier; Michel Aptel (Perspectives Interdisciplinaires sur le Travail et la Santé)
Rotation is often perceived by companies as one answer to preventing musculoskeletal disorders (MSD) because it offers both biomechanical and psychosocial variability in job requirementsTwo job rotation systems were compared in the context of an upper-limb MSD prevention process. Two methods were used, one assessing the efforts and postures of the dominant shoulder, and the other, the subjective evaluation of the difficulties in job performance (work pace, learning and risk of error). These evaluations and the MSD complaints expressed by the operators were compared. After these two methods were implemented, one of the two job rotation systems stood out due to a significant postural risk factor and a significant risk of error. The outcome of the project was some recommendations for job rotation in order to prevent MSD.